Association of Elevated Blood Pressure in the Emergency Department With Chronically Elevated Blood Pressure - Poon, Sabrina J. (J Am Heart Assoc, 2020)
BACKGROUND: Emergency department (ED) visits for hypertension are rising, but the importance of elevated blood pressure (BP) measured during the ED visit is controversial. We evaluated the relationship between ED BP and mean BP over the subsequent year. METHODS AND RESULTS: We performed a retrospective cohort study from January 1, 2010 to December 31, 2013 of 8105 adult patients who made 1 visit to an academic medical center ED with ≥2 ED BPs and ≥2 BPs measured in the subsequent year. The primary exposure was lowest ED systolic BP. The primary outcome was mean systolic BP ≥140 mm Hg over the year following the index ED visit. Diastolic BP was examined as a secondary exposure and outcome. Multiple logistic regression was performed adjusting for several covariates, with interaction terms for hypertension diagnosis, ED disposition, pain‐related ED chief complaint, and sex. Patients whose lowest ED systolic BP was 140 to 159 mm Hg had an adjusted odds ratio of having a mean SBP ≥140 mm Hg in the subsequent year of 10.9 (95% CI, 7.6–15.6). Patients without diagnosed hypertension and ED BP 140/90 to 159/99 mm Hg were more likely to have elevated BP in the following year. Hospitalization increased the likelihood of persistently elevated systolic BP but not diastolic BP. There was no effect modification by pain‐related ED complaint. CONCLUSIONS: When ED BP is consistently elevated, BP is highly likely to remain elevated in the subsequent year, regardless of pain, and particularly among patients without diagnosed hypertension. Further research is needed to determine the optimal management of elevated ED BP.